2006
DOI: 10.1504/ijlsm.2006.010382
|View full text |Cite
|
Sign up to set email alerts
|

An information technology implementation framework for the logistics industry in Singapore

Abstract: An industry cluster is a geographically concentrated, self-flourishing ecosystem comprising production systems, shippers, logistics service providers, IT vendors, infrastructure providers, regulatory agencies, research institutions, consultants and other logistics-related organisations that leverage on the interdependencies between them to provide efficient and effective logistics solutions. This article introduces a framework in the deployment of supply chain technologies for the logistics industry. More spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Based on the bibliographic review, 22 ICT implementation models were identified; among them, those proposed by Ruta (2005), Tan and Kritchanchai (2006) and Madritsch and May (2009). The technologies deployed were varied, including enterprise resource planning systems (ERP), barcode, e‐procurement, etc.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the bibliographic review, 22 ICT implementation models were identified; among them, those proposed by Ruta (2005), Tan and Kritchanchai (2006) and Madritsch and May (2009). The technologies deployed were varied, including enterprise resource planning systems (ERP), barcode, e‐procurement, etc.…”
Section: Resultsmentioning
confidence: 99%
“…According to Grohowski et al (1990), a new module should only be implemented after the last activity of the previous implementation has been performed. We also propose that there should be a feedback for ICT integration with its external partners: these partners should also be included gradually, like the ICT modules (Fu et al , 2004; Tan and Kritchanchai, 2006). Figure 3 shows where to place the two proposed feedback steps in the implementation process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation